Предмет: Алгебра,
автор: Аноним
600 – (8 – z)(z²+8z + 64).
упростить
Ответы
Автор ответа:
2
Ответ:
600 – (8 – z)(z²+8z + 64).=600-+8z²+64z+512-z³-8z²-64z)=600-(512-z³)=600-512+z³=88+z³
Автор ответа:
3
Ответ:
600 – (8 – z)(z²+8z + 64)
600-(8z^2+64z+512-z^3-8z^2-64z)
600-(512-z^3)
600-512+z^3
88+z^3
Это все можно в строчку записать,но я записала чтобы было понятнее.
Похожие вопросы
Предмет: Алгебра,
автор: dayana3008
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: rafikchannel6
Предмет: Математика,
автор: Drugru